Spatio – Temporal Changes of Iran Inland Precipitation during Recent Decades - hosein Asakereh (جغرافیا و توسعه, 2007)
Due to importance of precipitation spatio-temporal changes have been done many study approach. Some of these approaches are relay on complex geostatistics and classical statistic technique. The result of these kind is isohyets map and their characters. Based on monthly data of 152 synoptic and 170 climatologic stations during 1961 to 2003 spatio-temporal changes of Iran precipitation on 8012 pixel was analyzed by mixed methods of geostatistical and classical approaches. According to the Kriging method, the isohyets map of Iran inland and the map of changes created as the value of changes. About 51.4% of the country area suffered from the changes especially in the mountain regions. The rate of changes is 29.6 to -15.7 mm per year that happened in Koohrang and Ardabil-Khalkhal region respectively. The relationships analysis shows the changes happened in the mountain and the western part of the country.